The importance of landscape diversity for carbon fluxes at the landscape level: small‐scale heterogeneity matters. (7th April 2016) - Premke, Katrin; Attermeyer, Katrin; Augustin, Jürgen; Cabezas, Alvaro; Casper, Peter; Deumlich, Detlef; Gelbrecht, Jörg; Gerke, Horst H.; Gessler, Arthur; Grossart, Hans‐Peter; Hilt, Sabine; Hupfer, Michael; et al.
Abstract : Landscapes can be viewed as spatially heterogeneous areas encompassing terrestrial and aquatic domains. To date, most landscape carbon (C) fluxes have been estimated by accounting for terrestrial ecosystems, while aquatic ecosystems have been largely neglected. However, a robust assessment of C fluxes on the landscape scale requires the estimation of fluxes within and between both landscape components. Here, we compiled data from the literature on C fluxes across the air–water interface from various landscape components. We simulated C emissions and uptake for five different scenarios which represent a gradient of increasing spatial heterogeneity within a temperate young moraine landscape: (I) a homogeneous landscape with only cropland and large lakes; (II) separation of the terrestrial domain into cropland and forest; (III) further separation into cropland, forest, and grassland; (IV) additional division of the aquatic area into large lakes and peatlands; and (V) further separation of the aquatic area into large lakes, peatlands, running waters, and small water bodies These simulations suggest that C fluxes at the landscape scale might depend on spatial heterogeneity and landscape diversity, among other factors. When we consider spatial heterogeneity and diversity alone, small inland waters appear to play a pivotal and previously underestimated role in landscape greenhouse gas emissions that may be regarded as C hot spots. Approaches focusing on the landscape scale will also enable improved projections of ecosystems' responses to perturbations, e.g., due to global change and anthropogenic activities, and evaluations of the specific role individual landscape components play in regional C fluxes. WIREs Water 2016, 3:601–617. doi: 10.1002/wat2.1147 This article is categorized under: Water and Life > Nature of Freshwater Ecosystems Science of Water > Water and Environmental Change Science of Water > Water Quality